P systems with picture objects - Krishna, Shankara Narayanan; Rama, Raghavan; Krithivasan, Kamala (Acta Cybernetica, 2001)
New computability models called P systems, based on the evolution of objects in a membrane structure, were recently introduced. In this paper, we consider two variants of P systems having "complex objects" like pictures as the underlying data structure. The first variant is capable of generating pictures with interesting patterns. We also investigate the generative power of this variant by comparing it with the families of two dimensional matrix languages. The second variant has some applications in pattern generation.